Religion and the public order of the European Union - McCrea, Ronan (Oxford : Oxford University Press, 2011)
The first account of the relationship between religion and the constitutional order of the EU, dealing with the key questions of religious freedom and the institutional role of religion and addressing the issues that are at the centre of public debate in Europe, such as the compatibility of Islam with European models of liberal democracy.
Includes bibliographical references.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Jan. 12, 2011).
Keywords: Church and state -- European Union countries; Liberty -- Religious aspects; Religion and law -- European Union countries; Public policy (Law) -- European Union countries